Implementing Children’s Songs as a Teaching Medium in Elementary School English Instruction - Setyadi, Rinanto Fahmi; Muamaroh, Muamaroh (Universitas Muhammadiyah Barru, 2025)
This resarch aims to find out how teachers implement children’s songs as English teaching media, the obstacles faced by teachers in implementing them, and the solution taken by the teachers. The research design of this study was descriptive qualitative. The subjects were 2 teachers at one of elementary schools in Solo. The data was collected through classroom observations and structured interviews. Data were analyzed qualitatively. The results showed that songs are used as teaching media with learning procedures that include opening, core activities, and closing, teachers use materials taken from the books, teachers used blackboards as learning media and teachers evaluated by giving questions at the end of learning. The teachers selected the easier songs to make students understand. The teachers sang the songs themselves as the example for the students then students sang it together after the teacher. The teachers translated the lyrics. In teaching children’s songs as media the problems faced by the teachers were: mispronunciation for some words, students' lack of confidence, students' inability to concentrate in learning, and select the appropriate songs. The solutions were teacher correct mispronounciation directly and the end of lesson, the students sang in a group, the teachers conduct interactive teaching, and modification of songs. In conclusion children's songs can be an effective tool for supporting early English language learning. Interactive learning and selection of suitable song material is the key to its success.